The Analysis of the Effectiveness of SMPIT Tunas Cendekia Profile Videos as Digital Promotion Media: Mixed Method Approach with Epic Model, Qualitative Interviews, and Youtube Analytics - Hariadi, Rudi; Yeni (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
In the era of digital competition, educational institutions are required to adopt innovative and technology-based promotional strategies. This study aims to evaluate the effectiveness of a school profile video of SMPIT Tunas Cendekia as a digital promotional medium to support student enrollment campaigns. A mixed-method approach was applied by integrating the EPIC Model (Empathy, Persuasion, Impact, Communication), qualitative interviews, and YouTube Analytics. Quantitative data were collected from 66 respondents using a Likert-scale questionnaire based on the EPIC Model, while qualitative insights were gathered through in-depth interviews with prospective parents and school representatives. Additionally, YouTube performance metrics such as view count, watch time, and click-through rate (CTR) were analyzed. The findings show that all four EPIC dimensions scored in the "Highly Effective" category, with an overall EPIC Rate of 4.26. Interview results confirmed strong emotional resonance, increased interest, and a positive perception of the school’s image. YouTube data indicated solid engagement, with a CTR of 4.39% and an average watch duration of 2 minutes and 44 seconds. The integration of audience perception, qualitative insight, and digital metrics provides comprehensive evidence that profile videos serve as an effective communication tool in educational marketing. This study recommends content enhancements based on audience needs to improve future promotional efforts.